Women Empowerment through Panchayati Raj Institutions with Reference to Silchar and Lakhipur Development Blocks under Cachar District - Singha, Y. Monojit (International Journal of Psychosocial Rehabilitation, 2020)
Though many laws have been enacted not only at the national level but also at the international level, women could not occupy an equal role in the decision-making processes across the world. Even in the post 73rd Amendment of the Constitution of India, the role of women in its democratic decision-making is not satisfactory. When we talk about the status of women in the Indian society, the most important aspect that comes to mind is patriarchy. This paper tries to look at the initiatives of the Government of India to improve the condition of women through the prism of Panchayati Raj Institutions. It also looks at the working of these institutions in the post 73rd Amendment, towards the empowerment of women by taking a case study of the Cachar district with special reference to Silchar and Lakhipur development blocks.The paper focuses on the obstacles faced by women representatives in the Panchayats and highlights the factors which overtly or covertly tend to prevent women members from performing their roles.